Design and Development of Cost-Effective Automatic Location Identification for Campus Monitoring - Abidin, W.A.W.Z; Othman, A.K.; Hong Ping, Kismet; Masri, T.; Zamhari, N. (IEEE, 2010)
Untraceable theft equipment is one of the problems faced by university campus. Some of these stolen equipments are untraceable due to their small size and portability. Lack of real-time notification and tracking ability of the stolen equipment prevents prompt and effective actions to be taken. Therefore, an system needs to be deployed within the campus that makes it possible to track down equipments once they are stolen. The purpose of this research work is to design and develop automatic location identification (ALI) system for security purpose based on the GPS technology. The coverage area of the tracking is within the Universiti Malaysia Sarawak (UNIMAS) area. This research work involves stages such as creating an electronic map of the campus, identification and set up of the hardware that is used to communicate between the GPS receiver and the server and finally developing a program that can perform the calculation and mapping operations. Research methodology will be explained in this paper and detailed process of the development of the system will be described. The developed system allows real-time notification in the event of equipment being stolen and has the ability to perform automatic tracking once the equipment is taken away from a predetermined parameter. It also has function that can record the movement history of the equipment for the purpose of later analysis. Due to its simplicity and low-cost, the system can be easily developed and applied in order to prevent the occurrences of equipment being stolen.